Reformation of the judicial appraisal adoption system used by party institutions entrusted by the investigation agency in criminal proceedings - Yang Lian; Mengshang Wu; Yuanyuan Lian (Journal of Forensic Science and Medicine, 2019)
The new requirements of trial-centered litigation in China are a concrete manifestation of the reform of the rule of law under Xi Jinping's new socialist era. The effective implementation of judicial appraisal lays a solid foundation for the correct identification of facts, accurate conviction, and sentencing, and technically, it should guarantee a fair trial. However, in practice, judicial appraisal opinion carries the risk of a diminished trial that deviates from the trial-centered requirement to substantiate a charge and can easily lead to unjust cases. This paper seeks to discuss the system of identification of property loss involved in criminal proceedings, which is implemented by a third-party appraisal institution entrusted by the investigation agency, and highlights the fact that the third-party appraisal institutions in judicial practice are currently reliant on cooperative thinking, but countenance the lack of a mechanism for effective accountability, and the court's propensity for their support. This leads to the verification components of the trial being depreciated, which may lessen the validity of the appraisal opinion (substantiation). In response to this problem, the author hopes to provide some suggestions to assist third-party appraisal agencies in the completion of judicial appraisal and achievement of their trial-centered reform goal by rationalizing the relationship between the investigation agency and identification institution, establishing a hierarchical accountability mechanism, and improving the rules governing testimony in court.